The new ESA/IRS pricing scheme : a comparison with dialog - JACK, R. F (Online (Weston, Conn.), 1990)
The new ESA-IRS pricing scheme for accessing its on-line data base is described and actual charging rates are published for 78 data bases giving: on-line session rates; on-line hourly rates; and display charges per record (for SCAN, BROWSE, BROWSE ABS, and REF OR ALL). ESA and DIALOG charges, for 36 data bases, are compared in terms of session rates, hourly rates and full citation rates (for ESA-IRS) and connect hour and full citation rates (for DIALOG). Detailed cost of searching ABI/INFORM and INSPEC on ESA-IRS and DIALOG at 1200 baud and 2400 baud suggests that it may be cheaper to search ESA-IRS using 1200 baud and cheaper to search DIALOG using 2400 baud. 00 N.L.M.